PENGARUH LAYANAN INFORMASI KARIR TERHADAP TINGKAT PERENCANAAN KARIR PESERTA DIDIK KELAS XI IIS DI SMA NEGERI 2 PEKANBARU - Hayati, Hamda Silfi; Umari, Tri; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Career information services is very important provided to students, to help students understand and evaluate the job market information and make choices related to the world of work. This study aims to determine the effect of engineering career information services to the improvement of career planning of students of class XI IIS SMA Negeri 2 Pekanbaru. The method used is a true-experimental method with the pattern of pretest-posttest control group design. The subjects of this study are students of class XI IIS Negeri 2 Pekanbaru with a low level of career planning. Based on the correlation coefficient between x1 and x2 is the determinant coefficient of 0.75 and r2 = 0.56. This means that the contribution of information services career to career planning by 56%. Paired t test of calculation Sample t-test, t obtained > t table (8.811> 2.042) so the hypothesis is accepted, so there are differences in the level of students' career planning in class XI IIS SMA Negeri 2 Pekanbaru before and after a career information service.Keywords : information services, career planning